Metformin-Associated Lactic Acidosis (MALA). Our experiencie and a review - Enrique Chicote-Álvarez; Helena Camino-Ferró; Marlene Feo-González; Maite Arlabán-Carpintero; Natalia Gloria Lizama-Gómez (Iberoamerican Journal of Medicine)
Introduction: Metformin (a biguanide) for the treatment of Type 2 Diabetes Mellitus is widely used worldwide. However, is a double-edged sword for critically ill patients. One of the most important problems with its use is the risk of developing metformin-associated lactic acidosis (MALA). We present our 10-year experience with lactic acidosis attributed to MALA as well as a review of the literature. Material and methods: We reviewed admissions to the Intensive Care Unit (ICU) of a secondary-level hospital (630 inpatient beds) with diagnoses of "metabolic acidosis," "lactic acidosis," and "metformin-associated lactic acidosis" from January 2014 to June 2024. Data were collected from patients' electronic medical records and entered into an Excel® document for analysis. Results: Of the total 72 cases reviewed, 11 were included. Nine cases were male (81.82%), with a mean age of 75.36 years (ages ranging from 63 to 80 years). None of the cases had a history of chronic kidney disease, but all presented with acute renal failure. Renal replacement therapies (RRT) were used in all cases, with 6 patients initially treated with and 9 patients with conventional hemodialysis. The mortality rate was 0%. However, in the literature MALA presents a mortality exceeding 10% according to several studies. Conclusions: MALA is a very serious condition and early diagnosis is very important. The use of renal replacement therapies is of Paramount importance as well as clinical suspicion.